Genre-Specific Writing Instruction: a Contemporary Perspective - Kalynovska, Iryna (Навчально-науковий інститут філології Київського націона- льного університету імені Тараса Шевченка, 2023)
In recent years, the landscape of teaching English genre-specific writing has undergone a significant transformation, marked by a change from traditional methods to contemporary approaches. This paradigm shift reflects a growing awareness of the dynamic nature of writing genres in today’s diverse and rapidly changing communication environments.
The purpose of our research is to highlight the development of English genre-specific writing instructions, underlining the importance of writing genre combinations for students’ successful written communication.
Keywords: жанрове письмо; genre-specific writing; завдання з письма; writing instructions; навчання письма; teaching writing; жанр; genre; описове письмо; descriptive writing; пояснювальне письмо; expository writing; 37.016:811